Low back pain and perceived psychological workload among electricians - I. Sellami; A. Feki; A. Abbes; S. Baklouti; M. L. Masmoudi; K. Jmal Hammami; M. Hajjaji (European Psychiatry, 2024)
Introduction Low back pain (LBP) is a serious threat to electricians. It is well known that LBP is associated with physical strain. But the impact of psychological workload on the occurrence of LBP needs further investigation.